(untitled) - Cameron, Michelle H. (St. Louis, Mo., 2003)
This straightforward and accessible guide teaches the how and why for effective and safe application of physical agents within a complete rehabilitation program. It covers everything from new applications to thermal agents, hydrotherapy, traction, compression, ultrasound, electrical currents, and electromagnetic radiation. Readers will learn when and when not to use physical agents, how to integrate these tools into a patient's overall treatment plan, and how to document treatment to optimize reimbursement and minimize liability. Clinical case studies are streamlined to provide accurate information quickly while enhancing decision-making skills.
Keywords: Physical therapy,Vật lý trị liệu